Diastolic and systolic blood pressure and gout: a Mendelian randomization study - Li, Yanfang; Xie, Yufeng; Li, Jun; Chang, Zhichun; Zhang, Jianmei; Zhou, Zunming; Ren, Rong; Chen, Yun (Frontiers in Endocrinology, 2024)
Background Although there is solid epidemiological evidence supporting the connection between hypertension and gout, little has been said about the relationship between diastolic and systolic blood pressure and gout, the causal relationship and direction associated are uncertain, so we aim to research the causal relationship between diastolic and systolic blood pressure and gout. Methods We conducted a two-sample Mendelian randomization (MR) analysis to assess the causal effect between 2 blood pressure phenotypes (including diastolic blood pressure and systolic blood pressure) and 5 gout phenotypes (including gout, drug-induced gout, idiopathic gout, unspecified gout, and strictly defined gout) using genome-wide association study statistics. The inverse variance weighting method was used to generate the main results, while sensitivity analyses using MR-Egger, weighted median, Cochran’s Q test, Egger intercept test, and leave-one-out analysis, were performed to assess the stability and reliability of the results. Results After the screening, we found a causal relationship between diastolic blood pressure and gout, idiopathic gout, unspecified gout, and strictly defined gout, and a causal relationship between systolic blood pressure and gout, idiopathic gout, unspecified gout, and strictly defined gout. Conclusion From a genetic predisposition, controlling blood pressure may reduce the risk of gout.